Gambaran length of stay pada pasien stroke rawat inap di RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2015-Juni 2016 - Amiman, Reunita C.; Tumboimbela, Melke J.; Kembuan, Mieke A.H.N. (e-CliniC, 2016)
Abstract: Stroke is a cardiovascular disease which is the second rank of worldwide disease leading to death. Hospitalization is a treatment process which including patient to stay at hospital and length of stay (LOS) is a calculated time periode when patient admitted until discharged. This studywas aimed to obtain the profile of hospitalized stroke patientsâ€™ LOS at Prof. Dr. R. D. Kandou Hospital Manado from July 2015 to Juni 2016. This was a descriptive retrospective study using secondary data of the medical records. Samples consisted of 293 patients.The results presented ischemic stroke in 58.02% with LOS 6.84 days and hemorrhagic stroke in 41.98% with LOS 10.84 days. Patients with the highest LOS were females with hemorrhagic stroke (11.04 days); age 45-54 years (9.47 days); hemorrhagic stroke with hypertension (11.26 days); hemorrhagic stroke without dyslipidemia (10.67 days); hemorrhagic stroke with DM type 2 (12.67 days); and hemorrhagic stroke with tuberculosis (23.50 days). Conclusion: In this study, hemorrhagic stroke patients had higher LOS.Keywords: stroke, length of stay.Â Abstrak: Stroke adalah penyakit kardiovaskular yang menempati peringkat kedua sebagai penyakit yang menyebabkan kematian di dunia. Pelayanan rawat inap merupakan proses perawatan pasien dengan menginap di rumah sakit dan length of stay (LOS) merupakan periode yang dihitung ketika pasien masuk hingga keluar dari rumah sakit. Penelitian ini bertujuan untuk mengetahui gambaran LOS pada pasien stroke rawat inap di RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2015-Juni 2016. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data sekunder pasien stroke periode Juli 2015-Juni 2016 dari bagian rekam medik. Sampel penelitian berjumlah 293 pasien. Hasil penelitian menunjukkan persentase jumlah pasien stroke iskemik 58,02% dengan LOS 6,84 hari dan persentase jumlah pasien stroke hemoragik 41,98% dengan LOS 10,64 hari. Pasien stroke dengan LOS tertinggi terdapat pada jenis kelamin perempuan dengan stroke hemoragik, 11,04 hari; usia 45-54 tahun, 9,47 hari; stroke hemoragik dengan hipertensi, 11,26 hari; stroke hemoragik tanpa dislipidemia, 10,67 hari; stroke hemoragik dengan DM tipe 2, 12,67 hari; stroke dengan komplikasi, 9,33 hari; stroke hemoragik dengan pneumonia, 10,65 hari; dan stroke hemoragik dengan tuberculosis, 23,50 hari. Simpulan: Pasien stroke hemoragik memiliki LOS yang lebih tinggi.Kata kunci: stroke, lama rawat